The Role of Natural Geographical Factors in the Specialization and Development of Agriculture in Surkhandarya Region - Abdunazarov Husan Menglievich; Niyazov Khojakul Mirzoboboevich; Mustaev Kurbonmurod Rahmon ugli (Indonesian Journal of Innovation Studies, 2022)
This article describes the role and importance of agro-climatic factors of land and water resources in the specialization and development of agricultural sectors in Surkhandarya region.